2013
DOI: 10.1146/annurev-publhealth-031912-114447
|View full text |Cite
|
Sign up to set email alerts
|

Routine Versus Catastrophic Influences on the Developing Child

Abstract: Exposure to toxic stress accelerates the wear and tear on children’s developing bodies and leaves a lasting mark on adult health. Prior research has focused mainly on children exposed to extreme forms of adversity, such as maltreatment and extreme neglect. However, repeated exposure to less severe, but often chronic stressors is likely to play as large, if not larger, of a role in forecasting children’s future mental and physical health. New tools from neuroscience, biology, epigenetics, and the social science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 132 publications
(153 reference statements)
1
53
0
Order By: Relevance
“…Our finding that the magnitude of the negative association between early adversity and telomere length decreased with increasing years since exposure suggests that telomere shortening might be reversible over time, underscoring the fact that additional life experiences contribute to overall health. In our review of the literature on telomeres and early adversity, there was little data regarding consistency of care providers, nurturing relationships, and other resilience-associated factors 69 . To better understand the impact of all exposures, future studies would benefit from a comprehensive examination of both adversity and resilience factors.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that the magnitude of the negative association between early adversity and telomere length decreased with increasing years since exposure suggests that telomere shortening might be reversible over time, underscoring the fact that additional life experiences contribute to overall health. In our review of the literature on telomeres and early adversity, there was little data regarding consistency of care providers, nurturing relationships, and other resilience-associated factors 69 . To better understand the impact of all exposures, future studies would benefit from a comprehensive examination of both adversity and resilience factors.…”
Section: Discussionmentioning
confidence: 99%
“…Given the starkly different etiologies and pathogenetic processes leading to organ failure in these diseases, the underlying neuropsychological and -biological mechanisms remain to be elucidated. Further research should also take into account that stress (44) and anesthesia (45,46) in early childhood may negatively affect brain development and consequently cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous research studies have revealed that both EF and prefrontal cortex are susceptible to adverse environmental conditions (e.g. Mezzacappa et al, 2001;Odgers & Jaffee, 2013). One condition that is believed to produce adverse outcomes which affect EF and prefrontal cortex is maternal depression.…”
Section: Introductionmentioning
confidence: 99%